Post-Photography - Bejenaru, Matei; Gheorghe, Cǎtǎlin (Iaşi : Universitatea de Arte George Enescu, 2015)
Bloomberg, Divine ; Chanarin, Oliver ; Bejenaru, Matei ; Schletterer, Nikolaus ; Batur Gökçeer, Cemil ; Magno, Marcela ; Gîrbovan, Bogdan ; Bressan, Michele
Matei Bejenaru – Editorial: Post-photography ; Catalin Gheorghe – Argument: The politics and quotidianity of the post-photographic image after the mutation of perceptivity ; Cristian Nae – The Flooded Camera: Post-Photography or Accelerationism 2.0?; Alfredo Cramerotti – The Hyerimage ; Corina Ilea – 29 September 2015, or the millions of photographs I’ll never get to see ; Adam Bloomberg & Oliver Chanarin – Divine Violence / Holy Bible ; Nikolaus Schletterer – Suspended. With a text by Andrei Siclodi ; Matei Bejenaru – Zone System ; Cemil Batur Gökçeer – Cave Albino ; Marcela Magno – Land ; Bogdan Gîrbovan & Michele Bressan – RAPI (Romanian Archaeological Photography Index) / Underground
boek